2022
DOI: 10.3389/fphar.2022.979307
|View full text |Cite
|
Sign up to set email alerts
|

The molecular pathogenesis of triptolide-induced hepatotoxicity

Abstract: Triptolide (TP) is the major pharmacologically active ingredient and toxic component of Tripterygium wilfordii Hook. f. However, its clinical potential is limited by a narrow therapeutic window and multiple organ toxicity, especially hepatotoxicity. Furthermore, TP-induced hepatotoxicity shows significant inter-individual variability. Over the past few decades, research has been devoted to the study of TP-induced hepatotoxicity and its mechanism. In this review, we summarized the mechanism of TP-induced hepato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 122 publications
0
7
0
Order By: Relevance
“…56 Previous studies have found that triptolide leads to hepatic oxidative stress via CYP2E1 and Nrf2. 13 Our results showed that hepatic oxidative stress increased in WT mice after triptolide administration, whereas the livers of CXCR3deficient mice did not exhibit oxidative stress, suggesting that CXCR3 was involved in triptolide-induced CLI through regulation of hepatic oxidative stress. Research has revealed that Egr-1 upregulation and AKT phosphorylation are the results of CXCR3 activation and result in ROS generation.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…56 Previous studies have found that triptolide leads to hepatic oxidative stress via CYP2E1 and Nrf2. 13 Our results showed that hepatic oxidative stress increased in WT mice after triptolide administration, whereas the livers of CXCR3deficient mice did not exhibit oxidative stress, suggesting that CXCR3 was involved in triptolide-induced CLI through regulation of hepatic oxidative stress. Research has revealed that Egr-1 upregulation and AKT phosphorylation are the results of CXCR3 activation and result in ROS generation.…”
Section: Discussionmentioning
confidence: 51%
“…Oxidative stress stimulates upregulation of the redox-sensitive transcription factors such as NF-κB, AP-1, and Egr-1 expression and increases cellular kinase transduction and phosphorylation of phosphatases, such as AKT . Previous studies have found that triptolide leads to hepatic oxidative stress via CYP2E1 and Nrf2 . Our results showed that hepatic oxidative stress increased in WT mice after triptolide administration, whereas the livers of CXCR3-deficient mice did not exhibit oxidative stress, suggesting that CXCR3 was involved in triptolide-induced CLI through regulation of hepatic oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Triptolide shows considerable potential for clinical application in the treatment of many diseases, with various effects including anti-inflammatory, anti-rheumatic, immunosuppressive and anticancer effects (Gao et al, 2021). However, its narrow therapeutic window, poor solubility and low bioavailability, multiple organ toxicity, especially hepatoxicity, limit its clinical applications ( Noel et al, 2019 ; Hu et al, 2022 ). The cell growth of oral cancer and HNSCC can be inhibited, which is related to a dose-dependent apoptosis induced by triptolide and its derivatives ( Chen et al, 2009 ; Caicedo-Granados et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%